Stability in ASEAN+3 exchange markets: An EGARCH-M approach - Rahman, Md. Saifur; Shahari, Farihana (World Scientific and Engineering Academy and Society (WSEAS), 2015)
This paper empirically investigates the advancement of exchange markets’ stability and comovement after the ASEAN+3 financial cooperation agreement. The study employs EGARCH-in-mean approach and uses daily exchange rates. The findings indicate that: 1) the exchange market volatility is resulted from regional markets’ shocks during both of pre and post-agreement periods, 2) the ASEAN+3 exchange markets progressed substantial development during post-agreement, 3) both of high and low income economies are improving the exchange market stability in a cooperative way regardless of income level, and 4) the overall impact of ASEAN+3 financial cooperation leads to stabilize the regional exchange markets.